Implementation of Jarimatika Method in Mathematics Subjects at MI Maarif NU Bentul to Improve Learning Motivation - Ariana, Uti; Rachmah, Uun Fitriana; Khasanah, Uswatun; Hasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to implement the Jarimatika method in Mathematics subjects in grade IV MI Ma'arif NU Bentul to improve student learning outcomes. Jarimatika is a finger-based calculation technique that helps students understand basic arithmetic operations faster and easier. This method is expected to improve students' understanding of Mathematics concepts and motivate them to learn more actively. The approach used in this study is quantitative with an experimental method. The subjects of the study consisted of two groups, namely the experimental group using the Jarimatika method and the control group using the conventional method. Data were collected through learning outcome tests before and after the implementation of the Jarimatika method, as well as through observation and interviews with teachers and students. The results showed that the implementation of the Jarimatika method significantly improved student learning outcomes compared to conventional methods. In addition, students who used this method were more motivated and showed a higher interest in learning Mathematics. Therefore, the Jarimatika method can be used as an effective learning alternative in improving Mathematics learning outcomes in elementary schools.